Exhaustive extraction of phenolics and tannins from some sun-exposed forbs and shrubs of the tropical Andes - Alonso Amelot, Miguel; Oliveros, Alberto; Arellano, Elida (Ciencia)
Monomeric and polymeric phenolic derivatives have attracted renewed attention due to novel discoveries and applications in the pharmaceutical and food industries. Although lower and higher plants generally synthesize these compounds as allomones, antioxidants, ultraviolet (UV) radiation filters, and for other purposes, relatively few species accumulate them in sufficient quantity to be of interest for industrial applications. For the most part these plants are woody perennials with long-lived leaves. Assuming that the metabolic investment of plants growing in high elevation regions is greater than that of lower areas due to the need to protect sun-exposed tissue to excess UV-B radiation and avoid the associated damage to DNA and free radical-mediated redox processes, we anticipated to find useful amounts of these materials in Andean forbs of low-mid stature and limited leaf longevity in western Venezuela where the UV-B contribution to solar radiation is high. Therefore the aims of this investigation were: 1) Select a group of representative Andean species of mid altitude flora in sun-exposed meadows. 2) Devise appropriate extraction methods to obtain the highest possible yield of phenolic and condensed tannins. 3) Compare the response of phenolic material during extraction depending on plant species. Eight plant species (Alnus acuminata, Clidemia ciliata, C. flexuosa, C. hirta, Miconia tuberculata, Monochaetum meridensis, and Psamisia penducifolia) of three distantly related dicotiledoneous families (Betulaceae, Ericaceae, Melastomataceae) and a fern (Pteridium arachnoideum) (Dennstaedtiaceae) growing at 2200 m above sea level and commonly found across the Andes were selected for study during the rainy season. Repeated sequential treatment of vacuum dried plant leaves and blending in 70% aqueous acetone at room temperature followed by sonication at 4-6°C was employed to obtain the phenolic-condensed tannin enriched extract. The monomeric and polymeric fractions were separated by exclusion chromatography and quantified by the modified Prussian Blue specrophotometric method. These species were found to contain elevated levels of phenolics (30-123 mg salicylic acid eq. g”“1 dw of leaf) and tannins (20-521 mg quebracho tannin eq g”“1 dw of leaf ) and to require between four and five consecutive extractions before a negative Prussian blue test of the extracted material could be attained. Single solvent treatments yielded only 21.1-80.3% of monomeric phenolics and 25.1-84.8% of condensed tannins, depending on plant species, although time of extraction did not improve yields. However, better yields were obtained by raising the volume/sample weight ratio from 70/5 (mL/g) to 140/5 although no further increments could be procured at higher ratios presumably because of inefficient blending of leaf particles suspended in the solvent. Surprisingly, C. flexuosa and M. meridensis furnished a higher yield of phenolics and tannins in the second extraction batch than in the first. To the competitive contribution of other more soluble solutes that are discharged in the first batch was attributed this odd behavior. We conclude that 1) plants growing in open areas at mid altitude in the tropical Andes contain a large proportion of phenolic/condensed tannin material. 2) These compounds need at least three and occasionally more sequential extractions for adequate removal from plant tissue and is strongly species dependent. 3) Solubility in aqueous acetone, adequate particle blending and competition by other components in the plant all contribute to extraction efficiency. 4) The high contents of phenolics and tannins found for the first time in some of these fast growing plants opens the possibility of their exploitation as new sources of these compounds.